The Value of Social Security: Are Formal Jobs Better? - Lucia Madrigal; Carmen Pagés; Agustina Suaya (Institute for the Study of Labor (IZA), 2016)
As the population ages, low and unequal social security coverage are among the most pressing challenges in the Latin American region. On average, only 45% of workers contribute to social security, and this figure is much lower for low-income and low-skilled individuals. There are many hypotheses for this limited and uneven coverage. This paper studies two of them: First, we test whether individuals do not contribute to social insurance because, due to myopia or limited information, they place little value in social insurance. Second, we test whether low-income, low-skilled individuals have a lower value of social insurance than higher-income or higher-skilled individuals. Using an indirect method to estimate individual social security valuation based on self-reported job satisfaction, we find that workers attain higher job satisfaction in formal than in informal jobs in Peru but not in the case of Mexico. In addition, we find little evidence that the value of social insurance increases with income or education. If anything, the opposite is the case, with lower-income or lower-education individuals deriving higher utility from having access to social insurance.
Keywords: J21; J28; O17; 330; job satisfaction; informality; social insurance; Latin America